Profil berpikir siswa SMP dalam menyelesaikan masalah matematika berdasarkan gender - Nuriansyah, Iffat Rahmadhani; Maf’ulah, Syarifatul; Masruroh, Faridatul (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2025)
Divergent thinking is characterized by thinking in all directions, always trying various solutions to solve problems, so several ideas or solutions emerge. Divergent thinking in this study is based on four aspects; fluency, flexibility, originality, and elaboration. This study used a descriptive qualitative approach with two subjects of class VIII students of SMP Negeri 1 Ploso Jombang in the academic year 2024/2025, male student are (BAE) and female student are (AN). Data collection technique for this research carried out by giving the DTT written test and interviews. Data were collected through the Divergent Thinking Test (DTT) and semi-structured interviews had been validated by experts. This research is a qualitative descriptive research. The selection of subjects in this study considering by gender. For data collection technique in this study using a DTT written test and interview. Data analysis method carried out with three stages of analysis. The results showed that the female subject (AN) excelled in all indicators of divergent thinking AN produced three different problem-solving strategies, such as calculating the area of the outer square minus the shaded area, dividing the square into two rectangles, and dividing the square into smaller elements. AN provided a detailed explanation in developing the solution. Subject BAE produced two strategies, which tended to be simpler and conventional, without much variation. In the aspect of problem solving based on Polya's steps (understanding the problem, planning the solution, executing the solution, and re-examining), both subjects could follow the steps. However, AN showed more depth in planning and re-examining, by exploring various alternative strategies and BAE was simpler in solving the problem and thought more efficiently.